2001
DOI: 10.1074/jbc.m104641200
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-mediated Dephosphorylation of Specific Histone H1 Isoforms

Abstract: We have previously shown a connection between histone H1 phosphorylation and the transcriptional competence of the hormone inducible mouse mammary tumor virus (MMTV) promoter. Prolonged exposure of mouse cells to dexamethasone concurrently dephosphorylated histone H1 and rendered the MMTV promoter refractory to hormonal stimulation and, therefore, transcriptionally unresponsive. Using electrospray mass spectrometry, we demonstrate here that prolonged dexamethasone treatment differentially effects a subset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Histones were then purified from co-extracted proteins, in particular HMG proteins, by gel exclusion chromatography on a Bio Gel P 100 column (46,47) and separated into two fractions: (a) main H1 histones and (b) H1°. The purity of the fractions was confirmed by MALDI-TOF mass spectrometry using a Voyager-DE Pro (Applied Biosystems, Framingham, MA), which showed four major peaks with m/z values in the range of 21,186 to 22,496, indicating that the main H1 histone subfraction contained H1.2-H1.5 and a single peak at 20,781 for the H1°subfraction, in close agreement with previously published data (48).…”
Section: Materials and Methods Preparation Of H1 Histonessupporting
confidence: 89%
“…Histones were then purified from co-extracted proteins, in particular HMG proteins, by gel exclusion chromatography on a Bio Gel P 100 column (46,47) and separated into two fractions: (a) main H1 histones and (b) H1°. The purity of the fractions was confirmed by MALDI-TOF mass spectrometry using a Voyager-DE Pro (Applied Biosystems, Framingham, MA), which showed four major peaks with m/z values in the range of 21,186 to 22,496, indicating that the main H1 histone subfraction contained H1.2-H1.5 and a single peak at 20,781 for the H1°subfraction, in close agreement with previously published data (48).…”
Section: Materials and Methods Preparation Of H1 Histonessupporting
confidence: 89%
“…19,20 From these studies, it was determined that specific mouse histone H1 isoforms showed differential changes in phosphorylation based on treatment. These data pointed specifically to the mouse H1.3, H1.4, and H1.5 isoforms as targets of CDK-specific phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, ions were observed which correspond in mass to all of the nonphosphorylated form of the peptides, whereas only masses corresponding to phosphorylated TPVK (m/z obs = 524.28), SPK (m/z obs= 411. 19), and SPAK (m/z obs = 482.19) were observed. No ions were observed which would correspond in mass to phosphorylated ATGAATPK or TPK.…”
Section: Identification Of H14 Phosphorylation Sites In Human Ul3 Cellsmentioning
confidence: 99%
See 2 more Smart Citations